2022
DOI: 10.1063/5.0105752
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 100 MeV high-energy proton irradiation on β-Ga2O3 solar-blind photodetector: Oxygen vacancies formation and resistance switching effect

Abstract: β-Ga2O3 based solar-blind photodetectors have strong radiation hardness and great potential applications in Earth's space environment due to the large bandgap and high bond energy. In this work, we investigated the photoelectric properties influence of β-Ga2O3 photodetector irradiated by 100 MeV high-energy protons which are the primary components in the inner belt of the Van Allen radiation belts where solar-blind photodetectors mainly worked. After proton irradiation, due to the formation of more oxygen vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In order to better prove the good photoelectric conversion ability of this device, its responsivity was calculated . The formula for the responsivity R of a photodetector is as follows: R = I light I dark P S …”
Section: Resultsmentioning
confidence: 99%
“…In order to better prove the good photoelectric conversion ability of this device, its responsivity was calculated . The formula for the responsivity R of a photodetector is as follows: R = I light I dark P S …”
Section: Resultsmentioning
confidence: 99%
“…9,23,24 Of course, for open space applications, much higher energies of particles and a much higher range of particles of interest is of interest. Such studies are being carried out for different semiconductors, the radiation tolerance of β-Ga 2 O 3 devices to protons in the 100 MeV–1 GeV range, 25,26 and to irradiation with high energy heavy ions have been published 27–29 and also demonstrate a high radiation tolerance of β-Ga 2 O 3 devices. Thus, comparing the radiation tolerance of γ/β-Ga 2 O 3 test devices to that of β-Ga 2 O 3 devices looks as a justified measure of the radiation-tolerance worthiness of the γ/β-Ga 2 O 3 samples in electronic sense.…”
Section: Introductionmentioning
confidence: 99%
“…14 Besides, when photodetectors operate in space environments or military systems, they are inevitably subject to irradiation damage and defects are formed in the devices. Chang et al 15 have studied the photoelectric properties impact on β-Ga 2 O 3 photodetector irradiated with 100 MeV protons, where these high energy protons are the main components in the inner belt of the Van Allen radiation belts. The experiments demonstrated that after proton irradiation, the number of oxygen vacancies increased significantly and increased the transportation of carriers’ transformation.…”
Section: Introductionmentioning
confidence: 99%